PEMANFAATAN BAHAN AJAR E-MODUL BERBANTUN APLIKASI CANVA DALAM PEMBELAJARAN MENULIS CERPEN MENGGUNAKAN MODEL DISCOVERY LEARNING PADA SISWA KELAS IX - Fitria Sulistia Anggraeni; Via Nugraha; Sary Sukawati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
One of the achievement of learning objectives is the use of teaching materials in an interesting and not monotonous way. The application of ICT in learning is able to attract and increase student learning motivation. In the 2013 curriculum students are required to be able to express ideas through writing. However, the problems that are often encountered in the field of writing skills are still considered difficult, especially writing short stories. The use of e-module teaching materials assisted by the Canva application is one of the solutions to solve this problem. The purpose of this research is to find out the results of the use of e-module teaching materials assisted by the Canva application in learning to write short stories using the discovery learning model. The method used is descriptive qualitative with  a  sample  of  class  IX students  at SMP  PGRI 168  Cikalongwetan  by  collecting  data  using observation,  validation  and questionnaire techniques.  The observation  results  show  that  students follow the learning with the syntax that has been prepared according to the lesson plans. The results of the validator obtained a value of 88%, which was feasible for use in the field and the results of the questionnaire showed that it was in the very good category, namely obtaining a value of 87%.